Akumulasi Logam Berat Timbal (Pb) dan Pengaruhnya Terhadap Histologi Akar Mangrove Avicennia marina (Forssk). Vierh. di Perairan Mangunharjo Semarang - Jupriyati, Ruri; Soenardjo, Nirwani; Suryono, Chrisna Adhi (977-2407769)
Mangunharjo areas water is an area of coastal waters and the sea which close to the settlement industry and community activities. Where feared result of industrial waste were dumped around it that cause pollution. One form of pollution is the waste produced in the form of lead (Pb) heavy metals is a heavy metal element that can not be broken down by natural processes. The existence of Pb in nature have an impact on coastal vegetation is mangrove. Mangroves are coastal ecosystems which have an important role in estuarine areas. Other mangrove function is to absorb organic and non-organic materials. The purpose of this research was to study the accumulation of lead (Pb) heavy metals in Avicennia marina mangrove roots and influences the type of heavy metal accumulation of lead (Pb) to root tissue in Avicennia marina waters Mangunharjo. This research was conducted with descriptive analytic method. The results showed the amount of heavy metals on the roots of Avicennia marina Pb higher than the Pb content of heavy metals in sediment and water indicating that these plants are able to accumulate heavy metals in the roots to absorb these elements in sediments and water. Observations cell histology showed no change in root tissues of Avicennia marina.